Analysis of Pacing Strategy in the 400 m Freestyle Race - Nazwa Sausan Nabila; Pipit Pitriani; Ivan Rivan Firdaus (Universitas Negeri Semarang, 2025)
Pacing strategy refers to how a swimmer distributes speed and effort throughout a race and is widely recognized as a key factor influencing performance in middle-distance swimming events. A proper pacing strategy allows a swimmer to balance initial speed with fatigue management, especially in races like the 400m freestyle that demand both speed and endurance. The purpose of this study was to investigate how pacing strategies are used in the 400 m free style swimming race by analysis of 50 m split times for male and female swimmers. The data was taken cross sectionally from the swimmers during the West Java Series 3 (WJS-3) Championship at SOR R.A.A Adiwijaya. A descriptive: quantitative study was carried out with 16 swimmers (8 male and 8 female). Splits times were measured manually by the use of a stopwatch at every 50 m over the whole length of the race. Split times were averaged as a group median and pacing strategy was determined using descriptive statistics. Results revealed that female swimmers employed a positive pacing strategy, involving fast speeds in the initial segment and a progressive slowing across the laps. Male swimmers revealed a parabolic pacing pattern of fast start, controlled middle segment and acceleration in the final part of the race, indicating possibly an attempt to enhance finishing outcome. These results seem to indicate that pacing strategies at regional competition level are based on fast start approaches, and training programmes should be designed in function of speed distribution and maintenance during the race.